Zingeving en contingentie in het levensverhaal van adolescenten: Een kwalitatief pilotonderzoek naar betekenisgeving bij adolescenten in het voortgezet onderwijs - van den Berg, Michiel Christiaan; Scherer-Rath, Michael (Religie & Samenleving, 2023)
This qualitative pilot study describes how adolescents reflect on experiences of contingency and life goals in the context of their life story. By means of semi-structured interviews, eight life stories were examined for meaning, life goals, worldview, (in)congruence and the degree of integration in their life story. It is the first time that research instrument LISA (Life In Sight Application) was used for this target group. The results of the study show that respondents have an interest in and are struggling with major events, even if the narrative is sometimes brief. Besides this, the need to live life based on one’s own values and goals is clearly present among the respondents, even though at times they find it difficult to formulate goals.